Preventive Health for Transgender Men and Women - Imborek, Katherine L.; Graf, Elizabeth M.; McCune, Kaitlyn (Seminars in Reproductive Medicine, 2017)
Transgender men and women experience an incongruity between their assigned sex at birth and their identified gender. Gender dysphoria is defined by the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5) as clinically significant distress or impairment resulting from misalignment in assigned and experienced gender. Transgender people have a history of negative experiences in health care and efforts should be made to create a welcoming environment through staff training, gender neutral restrooms, and gender inclusive electronic medical record systems. Transgender men and women face unique preventive health concerns in areas of metabolic screening, cancer screening, immunizations, and anticipatory guidance secondary to cross-sex hormone therapy, gender confirming surgical procedures, and certain high-risk behaviors. Here, the available data are reviewed and suggested best practices are outlined to optimize the preventive health for this patient population.
Keywords: transgender; gender dysphoria; preventive health